Impact of anemia on outcome of HIV-infected pediatric patients: A prospective observational study - Baraturam Bhagrati Bhaisara; Mona Gajre; Mamta Manglani; Minal Wade; Sujata Sharma (Wolters Kluwer Medknow Publications, 2019)
Introduction: Anemia has been widely reported to predict a poorer prognosis for HIV-infected patients, both in terms of progression to AIDS and in survival. This study aimed to determine the etiology of anemia and its immunological correlation in HIV-infected children. Materials and Methods: Four hundred and eighty-nine HIV-infected children were screened, of which 86 HIV-infected children with anemia were enrolled. Standard WHO definitions were used for anemia, HIV staging, and growth parameters. Chi-square test, t-tests, and univariate and multivariate logistic regression analyses were used to analyze the data. Results: Anemia was present in 17.58% (86/489) of HIV-infected children, including 84.6% with moderate anemia, 11.5% with severe anemia, and 2.32% with mild anemia. The mean hemoglobin (Hb) among patients with CD4 count <350 cell/mm3 was lower (7.90 g%) (standard deviation 1.48) compared to those having CD4 >350 cell/mm3 (P = 0.02). Children with severe immunological stage had a significantly lower mean Hb (adjusted estimate: −1.61, 95% confidence interval: −2.65, −0.56) compared to those who had normal immune status. No statistically significant differences in mean Hb at baseline when compared to various demographic and clinical characteristics were observed in unadjusted and adjusted regression models. Conclusion: Hb is an easy and inexpensive tool to measure and can be used for monitoring disease progression in a resource-limited setting.